POLITICAL RHETORIC AND THE FORMATION OF POWER LEGITIMACY : A SYSTEMATIC LITERATURE REVIEW AND A PROPOSED THEORETICAL FRAMEWORK - Nurrahman Nurrahman; Zeira Salim Ritonga; Rubino Rubino (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
This article examines how political rhetoric contributes to the formation of power legitimacy in contemporary political communication. Rhetorical scholarship has mapped persuasive strategies and linguistic devices in political speech, while discursive legitimacy studies have explained mechanisms of justification, yet the two traditions have rarely been connected explicitly. Using a qualitative conceptual approach grounded in literature review, this study synthesizes scholarship on classical rhetoric, critical discourse analysis, political legitimacy, discursive legitimation, and populism. The findings show that ethos, pathos, and logos operate in layered configurations across cognitive, moral, and pragmatic bases of legitimacy, and that contemporary political rhetoric functions bidirectionally, legitimizing political actors while simultaneously delegitimizing opponents, institutions, or competing narratives. Building on these findings, the study proposes the Layered Rhetoric-Legitimacy Framework, integrating rhetorical pillars, legitimation mechanisms, legitimacy bases, dual directionality, and temporal vulnerability, and offering an analytical tool for future empirical research on political speeches and digital political communication.